2019
DOI: 10.1063/1.5092872
|View full text |Cite
|
Sign up to set email alerts
|

Negative differential resistance and magnetotransport in Fe3O4/SiO2/Si heterostructures

Abstract: Charge transfer induced ferromagnetism and anomalous temperature increment of coercivity in ultrathin α-Fe 2 O 3 decorated graphene 2D nanostructures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Negative differential resistance (NDR) effect has been attracting much attention due to its wide application in circuit amplifiers, [1] oscillators, [2] memories, [3] logic functions, [4] etc. At present, the NDR effect has been found in many materials and their devices, such as germanium (Ge), [5][6][7][8][9][10][11][12][13] silicon, [14][15][16] transition metal oxides, [17,18] rubrene/Bi 2 Se 3 , [19] etc. Especially, the research on NDR of germanium (Ge)-based devices is important because of their strong compatibility with the existing semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%
“…Negative differential resistance (NDR) effect has been attracting much attention due to its wide application in circuit amplifiers, [1] oscillators, [2] memories, [3] logic functions, [4] etc. At present, the NDR effect has been found in many materials and their devices, such as germanium (Ge), [5][6][7][8][9][10][11][12][13] silicon, [14][15][16] transition metal oxides, [17,18] rubrene/Bi 2 Se 3 , [19] etc. Especially, the research on NDR of germanium (Ge)-based devices is important because of their strong compatibility with the existing semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%
“…Low field magnetoresistance has also been reported on this system, with a maximum value of 1.9% at 230 K applying a magnetic field of 0.05 T [26]. More recently, Li et al also reported negative differential resistance in Fe 3 O 4 /SiO 2 /p-Si heterostructures, which due to the folded current-voltage character opens the door to different applications such as oscillators, logic gates, and data storage devices [27]. Given the complexity of spin phenomena, several factors can be related with the inconsistent values reported.…”
Section: Introductionmentioning
confidence: 52%